PROBLEMS, ESSENTIAL NEEDS, AND GUIDELINES FOR QUALITY DEVELOPMENT OF TEACHERS’ LEARNING MANAGEMENT ACCORDING TO THE PERSPECTIVES OF TEACHERS AND SCHOOL ADMINISTRATIVE STAFFS IN NAKHON NAYOK - Chanpensri, Atcharawan; Thiamtham, Thattharit; Nuchprasop, Kasasorn; Kaewchote, Nantawan; Sae-iab, Prasert; Soparat, Sasithorn (Academic Journal Phranakhon Rajabhat University, 2021)
This research aimed to study problems, the essential needs, and the guidelines for quality development of teachers’ learning management according to teachers and school administrative staff’s perspectives in Nakhon Nayok. Mixed-method research was carried out, and focus group discussion was conducted two times. The informants included teachers and school administrative staff in the 2018 academic year, using a purposive sampling method. For quantitative research, questionnaires were used to obtain the responses from the teachers and the school administrative staff. The research population was 2,456 people, derived by simple random sampling; the sample group consisted of 948 respondents. The content analysis, frequency, percentage, mean, standard deviation, and modified priority needs index: (PNI Modified) were used for the data analysis. The results of this research were: 1. The problems which were found the most were 1) the parents worked far from home so they could not pay attention to the children’s study, 2) changing the Nation’s Educational Policy many times caused the lack of continuality, 3) the students were lack of responsibility and enthusiasm, 4) the teachers had to handle other responsibilities besides teaching, 5) Coupons for Teachers Project were not beneficial for teacher production and development, and 6) the community did not understand its role to support education. 2. Needs which were the most were 1) system development for selection and quota for students to be teachers from schools in the responsible area of Rajabhat University. (PNI = 0.686), 2) development of morals and clear life goals of students (PNI = 0.490), 3) the teachers’ need in participating in the administration (PNI = 0.214), 4) development of ethics, morals, and spirit of teachers (PNI = 0.181), 5) the schools wanted the community to support the education (PNI = 0.173), and 6) the parents’ participation in taking care of students (PNI = 0.025). 3. Guidelines for quality development of learning management were Model of Learning Development by Necessary Needs and Collaborative Based Learning the most were 1) arranging supervision and monitoring to develop teaching and instruction as well as learning management method to integrate with teachers’ knowledge, 2) cultivating morality in the aspect of discipline and responsibility, thinking skill, and learners’ life goal, 3) installation of internet system in schools, development of libraries and learning resources, 4) graduate teacher development in terms of being teacher, using schools as learning incubators to develop teachers, and cooperation development between supervisors and mentors, 5)promoting schools as learning resources of the community, creating a network of parents and the local community to take part in school activities, and promoting using learning resources outside schools.